STUDY OF RISK FACTORS AND LEPTOSPIRA DETECTION OF SANITARY WORKERS IN JAKARTA, INDONESIA - Muslimin Budiman; Syifa Melati Putri; Putri Medita Rachmayanti; Ramdesima Kasmir; Dian Widiyanti (Biomedika, 2022)
ABSTRACT Leptospirosis is zoonotic disease, caused by spirochete-bacteria Leptospira, transmitted by excreted urine of rodent into the environment. Sanitary workers had high-risk of Leptospira infection due to frequent exposure to contaminated environment, which could cause asymptomatic leptospiruria (the presence of leptospira in urine) and severe complications, such as chronic kidney disease. The aim of this study was to find leptospiruria in sanitary workers, using PCR method, targeting specific genes of Leptospira. Urine samples and questionnaires were obtained from fifteen sanitary workers. Samples were cultured in EMJH-broth with addition of 5-fluorouracil, incubated for 3 months and observed for growth of bacteria using dark-field microscope.  Identification of bacteria was performed by PCR, targeting lipl32, rrl, flaB, ompL1 genes, followed by sequencing using Sanger method, alignment using ClustalW and BLAST. The questionnaires result showed that 26,7% of respondent had medium level of risk factors, and 53,3% of respondent had applied good prevention for leptospirosis. Pearson correlation analysis showed that there was relationship between risk factors and prevention. Culture result showed growth in four samples, and analysis by PCR only showed rrl-PCR had expected amplicon. However sequencing result showed that the amplicon had 99% homogeneity to Pseudomonas stutzeri. In conclusion, Leptospira was not found in the urine of sanitary worker, might be due to applied good prevention for leptospirosis.Keywords: Leptospira, Leptospiruria, Sanitary Worker, Risk Factors ABSTRAK Leptospirosis adalah penyakit zoonosis, yang disebabkan oleh bacteria Leptospira Sp., ditularkan melalui urin hewan pengerat yang dikeluarkan ke lingkungan. Pekerja sanitasi memiliki risiko tinggi terinfeksi Leptospira karena sering terpapar lingkungan yang terkontaminasi, yang dapat menyebabkan leptospiruria (adanya liptospira dalam urin) tanpa gejala, dan komplikasi berat, seperti penyakit ginjal kronis. Tujuan dari penelitian ini adalah untuk menemukan leptospiruria pada petugas kebersihan, menggunakan metode PCR, menargetkan gen spesifik Leptospira. Sampel urin dan kuesioner diperoleh dari lima belas petugas kebersihan. Sampel dikultur dalam EMJH-broth dengan penambahan 5-fluorouracil, diinkubasi selama 3 bulan dan diamati pertumbuhan bakterinya menggunakan mikroskop medan gelap. Identifikasi bakteri dilakukan dengan PCR, menargetkan gen lipl32, rrl, flaB, ompL1, dilanjutkan dengan sequencing menggunakan metode Sanger, alignment menggunakan ClustalW dan BLAST. Hasil kuesioner menunjukkan bahwa 26,7% responden memiliki faktor risiko tingkat sedang, dan 53,3% responden telah menerapkan pencegahan leptospirosis yang baik. Analisis korelasi Pearson menunjukkan bahwa ada hubungan antara faktor risiko dan pencegahan. Hasil kultur menunjukkan pertumbuhan pada keempat sampel, dan analisis dengan PCR hanya menunjukkan rrl-PCR memiliki amplikon yang diharapkan. Namun hasil sekuensing menunjukkan bahwa amplikon memiliki homogenitas 99% terhadap Pseudomonas stutzeri. Kesimpulannya, Leptospira tidak ditemukan dalam urin petugas kebersihan, mungkin karena penerapan pencegahan leptospirosis yang baik.Kata kunci: Leptospira, Leptospiruria, Petugas Kebersihan, Faktor Risiko